2018
DOI: 10.3389/fmicb.2018.01523
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing (MLST) Genotypes of Candida glabrata Bloodstream Isolates in Korea: Association With Antifungal Resistance, Mutations in Mismatch Repair Gene (Msh2), and Clinical Outcomes

Abstract: Candida glabrata bloodstream infection (BSI) isolates from a particular geographic area have been reported to comprise a relatively small number of the major sequence types (STs) by multilocus sequence typing (MLST) analysis. Yet little is known about the characteristics of major ST strains of C. glabrata. To address this question in Korea, we investigated antifungal resistance and non-synonymous mutations of the mismatch repair gene (msh2 mutations) in C. glabrata BSI isolates, as well as associated clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 36 publications
13
44
1
Order By: Relevance
“…All 107 isolates exhibited the susceptibility of the wild type for VRZ, ITZ and AMB and two isolates (G53 and G103) showed intermediate susceptibility to MCF and AND (0.125 µg/mL and 0.25 µg/mL, respectively). The low rate or apparent absence of antifungal resistance observed in our study is consistent with a previous multicentre candidaemia study conducted in Turkey 31 as well as reports from several other Asian, 29,30,41,42,46 South American 47 and European 45,48‐50 countries; however, it is in contrast with the data from USA, where echinocandin resistance in C glabrata is a major public health problem 12 …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…All 107 isolates exhibited the susceptibility of the wild type for VRZ, ITZ and AMB and two isolates (G53 and G103) showed intermediate susceptibility to MCF and AND (0.125 µg/mL and 0.25 µg/mL, respectively). The low rate or apparent absence of antifungal resistance observed in our study is consistent with a previous multicentre candidaemia study conducted in Turkey 31 as well as reports from several other Asian, 29,30,41,42,46 South American 47 and European 45,48‐50 countries; however, it is in contrast with the data from USA, where echinocandin resistance in C glabrata is a major public health problem 12 …”
Section: Resultssupporting
confidence: 92%
“…We found a low level of antifungal resistance among isolates, which is consistent with a previous study performed in Turkey, 31 and showed that sequencing together with AFST could provide more reliable data to guide clinicians in their choice of treatment for patients with C glabrata candidaemia. Together with similar studies conducted in China, 40,41 USA, 23 South Korea, 30 India 42 and Iran, 29 our study should contribute to better understanding of clinical and microbiological profiles of C glabrata bloodstream isolates.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Importantly, we and others have found that different MSH2 genotypes are characteristic of distinct STs/clades, suggesting that different STs may have different propensity towards mutability and acquiring drug resistant gene variants [82,[94][95][96]. This is significant because the distribution of C. glabrata STs varies both by geography and over time.…”
Section: Micmentioning
confidence: 88%
“…and constitutes a normal floral yeast in the human gastrointestinal tract, urogenital tract, and oral cavity. C. glabrata causes critical BSIs in hospitalized patients (Byun et al, 2018) and yet, despite its increased incidence, little is known of its molecular structure, epidemiology, and basic biological properties. Its prevalence has increased in the last decade and these species now rank as the second most frequently isolated Candida spp.…”
mentioning
confidence: 99%